Correction of Dysbiosis in Diversion Proctitis: Possibilities of Intraluminal Sanitation and the Prevention of Complications after Reconstructive Surgery - V. S. Groshilin; D. V. Martynov; Yu. L. Naboka; M. Yu. Bakulyarov; G. A. Mrykhin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Background. Repeated surgical interventions aimed at the colostomy closure and restoration of intestinal continuity after obstructive resections are traumatic and complex reconstructive operations on the colon. The complications of recovery operations largely feature wound abscesses (30–60 %) and anastomotic leakage (5–23 %), with the mortality levels from these complications reaching 0.4–2.8 %. Pronounced dysbiotic changes, the progression of catarrhal or erosive diversion colitis and proctosigmoiditis are the risk factors for anastomotic leakage and postoperative bowel dysfunction. This determines the need for a therapeutic algorithm of intestine sanitation and the introduction of methods for preventing the anastomotic leakage after obstructive resection of the distal colon (Hartmann’s operation). Aim. To evaluate the capability and efficiency of the intraluminal application of rifaximin-α (Alfa Normix® preparation, Alphasigma company) as a sanitising intestinal antiseptic for relieving diversion colitis and prevening postoperative complications of restorative operations after obstructive resection of the colon (Hartmann’s operation).Material and methods. A prospective comparative controlled study of the results of surgical treatment in 63 patients was conducted. The patients were divided into 2 groups, which were compared using the case-control principle. The operations included the colostomy closure and the restoration of intestinal continuity by applying a colonic anastomosis. In group I (main group, 30 patients), the original “Method of postoperative prevention of colonic anastomotic leakage” (Russian patent No. 2523822) was applied. In the control group (33 patients), routine methods for preventing anastomotic leakage and antibiotic prophylaxis were used. A comparative analysis of the number and severity of purulent-septic complications (taking into account the possibility of their relief), as well as the quality and rate of intestinal dysbiosis relief and the manifestations of diversion proctitis, was carried out.Results. The main group indicated the best results in terms of the main analysed parameters, fewer complications and anastomotic leakage. Thus, the total number of complications in groups I and II was 16.7 % and 27.3 %, respectively. The proportion of complications associated with the anastomotic leakage, inflammatory changes in this area and impaired patency in groups I and II was 6.7 % and 12.1 %, respectively. Rifaximin-α (Alpha Normix®) intolerance and pathological reactions associated with its use were not observed. The possibility for effective relief of the violations of quantitative and qualitative composition of the microflora in the colon stump was revealed. The main group showed better results in terms of eliminating local manifestations of diversion colitis and anorectal dysfunction compared to group II, where traditional schemes of postoperative therapy were used.Conclusions. Intraluminal dosed use of the Alpha Normix® suspension with the rifaximin concentration of 100 mg per 5 ml is an effective method of postoperative prevention of purulent-septic complications associated with anastomotic leakage during reconstructive operations on the distal colon. The introduction of Alpha Normix® in the scheme of postoperative treatment allows its results to be stabilised due to the sanitation of the intestinal lumen, the elimination of dysbiosis, the relief of inflammatory reaction and the elimination of factors supporting the development of diversion proctitis.